IMPROVING THE STUDENTS’ VOCABULARY ACHIEVEMENT BY APPLYING TIC-TAC-TOE GAME - Rini Susanti; Zainuddin (Universitas Negeri Medan, 2013)
This study deals with improving the students’ vocabulary achievement byapplying Tic-tac-toe Game. The subject of this study was grade VIII1 2012/2013students of SMP Negeri 1 Payung, desa Batukarang. The total number of the classis 36 students. This study applied classroom action research which consisted oftwo cycles. Three meetings were for first cycle and two meeting for second cycle.The data were collected qualitatively and quantitatively. The data werequalitatively collected from questionnaires sheet and observation sheet, whilequantitatively from the scores of vocabulary tests; orientation test, test I, and testII. After analyzing the data, it was found that there was an improvement ofstudents’ vocabulary achievement. It was proven by the increasing of the meanscore of the students’ vocabulary scores in each test where mean score of the firsttest was 56.94, the second test (test I) was 69.30 and the third test (test II) was80.14.